2017
DOI: 10.1039/c7mt00042a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting the BfrB:Bfd interaction in Pseudomonas aeruginosa causes irreversible iron accumulation in bacterioferritin and iron deficiency in the bacterial cytosol

Abstract: Iron is an essential nutrient for bacteria but the reactivity of Fe2+ and the insolubility of Fe3+ present significant challenges to bacterial cells. Iron storage proteins contribute to ameliorating these challenges by oxidizing Fe2+ using O2 and H2O2 as electron acceptors, and by compartmentalizing Fe3+. Two types of iron-storage proteins coexist in bacteria, the ferritins (Ftn) and the heme-containing bacterioferritins (Bfr), but the reasons for their coexistence are largely unknown. P. aeruginosa cells harb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(108 citation statements)
references
References 56 publications
7
101
0
Order By: Relevance
“…The Fdx, PaBfd from Pseudomonas aeruginosa (Figs. S1 and S2) was chosen as a template for the investigation, since this protein has shown to interact with a Bfr [24], and was also suggested to be involved in iron reduction and release from the Bfr. The phylogenetic study revealed one clade of…”
Section: Screening For Ferredoxin Candidates In Nostoc Punctiformementioning
confidence: 99%
See 1 more Smart Citation
“…The Fdx, PaBfd from Pseudomonas aeruginosa (Figs. S1 and S2) was chosen as a template for the investigation, since this protein has shown to interact with a Bfr [24], and was also suggested to be involved in iron reduction and release from the Bfr. The phylogenetic study revealed one clade of…”
Section: Screening For Ferredoxin Candidates In Nostoc Punctiformementioning
confidence: 99%
“…Fdxs have also been suggested to be involved in Fe 2+ release Bfr by direct protein-protein interaction [47], and a Fdx from Pseudomonas aeruginosa has been shown to interact with, and reduce, the iron core of PaBfr in vitro [64,24]. The interaction of Fdx and Bfr is thus established, but the proteinprotein interactions that allow the reduction of the iron-core of Dps are still not known.…”
Section: Introductionmentioning
confidence: 99%
“…6 Their ability to lay down an iron-rich mineral inside a protein shell was one of the first indicators that ferritins had a role in iron storage, 4 though it is now not certain that is the primary function of all bacterioferritins. While bacterioferritin (BFR) in Pseudomonas aeruginosa does act as the general housekeeping store for iron, 7 in Escherichia coli it does not. 8 Both P. aeruginosa and E. coli contain another ferritin in addition to BFR, prokaryotic ferritin (Ftn), which is also a homopolymer of 24 subunits, 9 and it is Ftn that functions as the general housekeeping store for iron in E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…In a very recent GWAS study of lysosome function (Weber et al, 2020), it was shown that unloading of iron from transferrin and delivery of bioavailable ferrous iron (Fe 2+ ) to the cell was the single indispensable function of lysosomal acidity for cell proliferation. This remarkable finding was presaged by studies of the bacterium P. aeruginosa, where genetic deletion of a bacterioferrireductase (limiting cytosolic Fe 2+ ) produced acute iron starvation despite more than adequate Fe 3+ bacterioferritin stores (Eshelman et al, 2017). Elevation of cytosolic Fe 2+ may enable the survival of TKI-tolerant 'persister' cancer cells (Hangauer et al, 2017), which become uniquely reliant on the activity of GPX4, a lipid hydroperoxidase that protects from ferroptosis (Dixon and Stockwell, 2014;Stockwell et al, 2017).…”
Section: Introductionmentioning
confidence: 99%